Electronic Fetal Monitoring and Cesarean Birth: A Scoping Review. Issue 4 (December 2017) - Paterno, M.T.; McElroy, K.; Regan, M.
Abstract : ( Birth . 2016;43(4):277–284) In the United States, cesarean delivery is performed in more than 32% of all births and is widely recognized to be an overused procedure. Efforts to decrease the cesarean delivery rate have been limited, however, by the inability to pinpoint the causes of overuse. Recently, electronic fetal monitoring (EFM) has been linked to increased cesarean delivery rates. For this paper, a review was conducted to summarize studies examining EFM in the low-risk pregnant population to determine its effect on cesarean birth.